REVOLUTION 4.0. AS A NEW PARADIGM OF INVESTING IN MILITARY INNOVATION (INNOVATIVE ECONOMY, 2020)
Sokhatskyi O.Yu. REVOLUTION 4.0. AS A NEW PARADIGM OF INVESTING IN MILITARY INNOVATIONPurpose. The aim of the article is the theoretical substantiation and empirical confirmation of the hypothesis regarding the change of the paradigm of investment in military affairs in the conditions of Revolution 4.0. and the development of practical recommendations for the formation of a system of incentives for the introduction of military innovations in the new technological era in Ukraine on this basis.Methodology of research. The general scientific and special methods of research were used in order to achieve the goal and to solve the problems: theoretical generalization and scientific abstraction in determining the nature of the modern sixth generation war, the change of which was caused by the new technological era, known as Revolution 4.0.; systematic, historical and logical approaches for forming a hypothesis regarding the change in the paradigm of investment in military innovation of this era; complex analysis and synthesis in the process of comparing the costs of weapons and equipment of wars of the fifth and sixth generations; studying the practice of creating and implementing military innovation in countries that occupy leading positions in world military ratings; to develop recommendations for the creation of a holistic system for the creation and implementation of Revolution 4.0 innovations in Ukraine.Findings. It is found that in the second decade of the XXI century army from a closed organization turns to open the dominant institution of security sector state that is constantly accumulate sufficient scientific contributions to victory in the technological competition today and in the future, pereoriyentovuyuchy investment flows from traditional military weapons and equipment at the latest, which correspond to the realities of Industry 4.0. It is revealed that communicative systems have a sufficient level of accessibility even to secret segments of a military organization.It has been determined that the high technological level of modern armies requires the involvement of civilian specialties and specialists, which improves the connection of the military with the public and provides a broader perspective of their development and perception in society.Originality. The hypothesis concerning the change of investment paradigm in military innovations in the first decade of the XXI century was formulated and empirically confirmed. It is determined that Industry 4.0 becomes the basic trend in the development of military affairs.Practical value. The recommendations in the article on the creation of a special institution in Ukraine are proposed to find talented researchers and inventors at the stage of the formulation of ideas, helping them to protect their intellectual property and these developments and inventions, as well as bring them to production, will significantly accelerate these processes, as well as more rational use of limited military budgets.Key words: Revolution 4.0; Industry 4.0; military innovations; the war of the fifth generation; the sixth generation war; weapons of the era of cyber-physical systems and virtual reality.
Keywords: Key words; Revolution 4.0; Industry 4.0; military innovations; the war of the fifth generation; the sixth generation war; weapons of the era of cyber-physical systems and virtual reality.